Investigation of The Effects of Clopidogrel on Bronchial Smooth Muscle in Female Rats - Batmaz, Husna; Sayin, Orhan; Pervin, Mehtap; Bozyil, Ahmed Sait; Oz, Zeynep Dila; Hekim, Munevver Gizem; Kacar, Emine (Wiley, 2023)
[Abstract Not Available]
Keywords: Bronchus; Clopidogrel; Isometric contraction; Smooth muscle